EFFECT OF ADDING DEXMEDETOMIDINE VERSUS FENTANYL TO INTRATHECAL HYPERBARIC BUPIVACAINE ON SPINAL BLOCK FOR INFRAUMBILICAL ELECTIVE SURGERIES - Dr. Jayesh Hadiya; Dr. Bhushan Ambare; Dr. Monika Masare; Dr. Vinay Dhakate; Dr. Prashant Patil (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: This study was conducted to compare the two adjuvant agents, dexmedetomidine (5μg) and fentanyl (25μg) added to 15mg of 0.5% hyperbaric bupivacaine introduced intrathecally for infraumbilical surgeries.Methods: This was a hospital-based prospective, randomized clinical study conducted among 90 adult patients belonging to ASA Grades I and II of either sex undergoing elective infra-umbilical surgeries. The study was carried out in a tertiary care centre in the Department of Anaesthesiology of the Medical College and Hospital, from November 2011 to June 2013 after obtaining clearance from the institutional ethics committee and written informed consent from the study participants.Results: The mean time to achieve sensory regression to the T12 level in group C was shorter as compared to groups F and D and these differences were found to be highly significant statistically. The difference in the results between group D and group F was statistically significant, with group D having a longer duration of sensory block. The differences in mean duration of complete motor block, complete analgesia, and mean time of rescue analgesia between the three groups were found to be statistically highly significant. Thus, dexmedetomidine (group D) has a longer duration than bupivacaine (group C) and fentanyl (group F).Conclusion: Dexmedetomidine as an adjuvant significantly prolongs the duration of complete analgesia and the time of rescue analgesia as compared to fentanyl and bupivacaine. The postoperative analgesic requirement was less for dexmedetomidine as compared to fentanyl and bupivacaine, leading to improved quality of analgesia.